The Influence Of Tasks Division, Motivation, Competence, And Work Discipline On Teacher Quality At Smp Negeri 1 Ujanmas Muara Enim District - April Kohar; Subahri Madjir; Darmin Darmin (Penerbit Jurnal Indonesia, 2023)
This study aims to the effect of the division of tasks, Motivation, Competence, and Work discipline on the quality of teachers at state Junior High School 1 Ujanmas Muara EnimRegency. The type of research used in this study was quantitatipe research. The data in this study used primary data by using research Collection technugues and questioonnaires. The reserch used survey methods, thereserch respondent werw 35 techers. Questionnaire instruments regarding quality of work as related variable, divison of tasaks, motivation, competence, and work discipline as independent variables an the analisys tool of tasks partially has a signicante affect on quality of work competence partially has a signicante affect on quality and work discipline paertially andf correlation has a significante affect on the quality of Juniore high school teachers in Negeri 1 Ujanmas Muara Enim District.